Knowledge model for post‐disaster management - Kaklauskas, Artūras; Amaratunga, Dilanthi; Haigh, Richard (International Journal of Strategic Property Management, 2010)
The main aim of this research is to help post‐disaster managers to find most rational solutions by using advanced knowledge and developed Model. Post‐disaster management is shared, purposeful activities based upon the development of common understandings and interpretations of means and ends. Stakeholders generate the personal and group decisions which contribute to post‐disaster management success. This article describes the development (during EurAsia project) of a Knowledge Model for Post‐disaster Management based upon multiple criteria decision making theory. The developed Model involves six stages that help to determine rational post‐disaster management alternatives by evaluating post‐disaster management’ life cycle, stakeholders, micro and macro environment.First Publish Online: 18 Oct 2010